2004
DOI: 10.1074/jbc.m400908200
|View full text |Cite
|
Sign up to set email alerts
|

The Broad Spectrum Antiviral Nucleoside Ribavirin as a Substrate for a Viral RNA Capping Enzyme

Abstract: The broad spectrum antiviral nucleoside ribavirin displays activity against a variety of RNA and DNA viruses. A number of possible mechanisms have been proposed during the past 30 years to account for the antiviral activity of ribavirin, including the possibility that ribavirin might have a negative effect on the synthesis of the RNA cap structure of viral RNA transcripts. In the present study, we investigated the possibility that ribavirin can directly serve as a substrate for the vaccinia virus RNA capping e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
69
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 65 publications
(72 citation statements)
references
References 44 publications
3
69
0
Order By: Relevance
“…We therefore tested whether ribavirin-based analogs could functionally replace the 7-methylguanosine moiety of capped mRNA. Furthermore, viral capping enzymes can utilize RMP to form an RpppN cap on viral mRNAs (Bougie and Bisaillon 2004). We generated three versions of a firefly luciferase (F-luc) mRNA by in vitro transcription, incorporating the conventional m 7 GpppG structure, the RpppG structure, or GpppG (which does not bind eIF4E).…”
Section: Resultsmentioning
confidence: 99%
“…We therefore tested whether ribavirin-based analogs could functionally replace the 7-methylguanosine moiety of capped mRNA. Furthermore, viral capping enzymes can utilize RMP to form an RpppN cap on viral mRNAs (Bougie and Bisaillon 2004). We generated three versions of a firefly luciferase (F-luc) mRNA by in vitro transcription, incorporating the conventional m 7 GpppG structure, the RpppG structure, or GpppG (which does not bind eIF4E).…”
Section: Resultsmentioning
confidence: 99%
“…The broad-spectrum antiviral ribavirin triphosphate, a nucleoside analog, has also been shown to directly interact with the guanylyltransferase of vaccinia virus, thereby inhibiting the guanylylation of RNA transcripts (Bougie and Bisaillon 2004). However, because of the high overall similarity between viral and cellular GTases, it was initially suggested that mechanism-based inhibitors might not be specific and show adverse side effects on human cells (Bougie and Bisaillon 2004). Nonetheless, mounting evidence suggests that subtle structural and mechanistic differences exist between the RNA viruses and cellular GTases.…”
Section: Discussionmentioning
confidence: 99%
“…Within host cells, it alters GTP pool concentrations by inhibiting IMP dehydrogenase (IMPDH) (29,30). Other modes of action may include direct inhibition of the influenza virus RdRp (31,32) and interference with capping of viral RNA (33). Some data suggest that ribavirin affects inflammatory and T-cell responses in vivo (34)(35)(36).…”
mentioning
confidence: 99%